Analysis Of Power Generation Photovoltaic Array 9×10 Wp Under Shading Effect - Utami, Dwi Prima Putri; Rajagukguk, Antonius (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
There are several problems that can interfere with the performance of large-scale PV. One that enhances PV performance is shading on a PV module, that make interferes PV performance. This research studied about the effect of shading on the performance of large-scale PV systems through testing a 9 × 10 Wp miniature PV array and simulation using Matlab software. The use of diodes on a PV module can be done to prevent damage to the PV module due to shading. Through the power-voltage (P-V) and current-voltage (I-V) characteristic curves the effect of shading and the use of bypass and blocking diodes can be determined. Shading effect gave in a decrease in power in the PV module. From the results of this study note that the bypass diode and blocking diode output power generated by the PV module can be optimal.